Students' Issues with Writing Analytical Exposition Text in Vocational School - Dewi Sartika; Sri Wuli Fitriati; Suwandi Suwandi; Hendi Pratama (International Conference on Science, Education, and Technology, 2023)
Writing is the most difficult productive skill to master when studying English. To assist students in improving their writing, teachers should be aware of their students' issues. The goal of the study was to highlight the issues that students at vocational schools have when producing analytical exposition texts. A case study with a qualitative design was used in this investigation. To take part in the study, a total of 25 eleventh graders from a vocational school in South Sumatra, Indonesia, were hand-selected. Data for this study were gathered using a closed-opened questionnaire and a writing exam. To assess the data from the writing exam and closed-ended questionnaire, this study used coding, category development, category description, and data interpretation based on Merriam's (2009) theories. They follow the same procedures as the thematic analysis. The findings revealed that, on average, 33.7% of students at vocational institutions found it challenging to create analytical exposition writings. The vocational school's students struggled with vocabulary, organization, mechanics, language use, and content. Their reading habits, low motivation, and low self-esteem regarding their writing abilities were other contributing factors to their writing problems. This discovery should contribute to addressing such issues by providing an efficient method that aids students in producing their analytical exposition texts.